Boundaries between Fair and Harmful Tax Competition - Szwajdler, Paweł (Journal of Education, Health and Sport, 2016)
The aim of this paper is to show boundaries between fair and harmful tax competition. The author analyses OECD’s reports and literature related to the tax competition. In the beginning, the author presents the notion of tax competition and its division into fair and unfair tax competition. Differences between tax heaven and preferential tax regime are also discussed. In the summary, the author highlights that boundaries between fair and harmful tax competition are not obvious, but there are well-known guidelines, which let distinguish above-mentioned issues. The author considers that there are real tax burden, effective exchange of tax information and transparency in the fair tax regime. The author states that taxpayer can do justified tax planning in such tax system.